Analysis of raw material inventory control for hinge upper assembly products using the economic order quantity method - Rifda Ilahy Rosihan; Suci Trisa Kartika; Jasan Supratman; Paduloh; Ratih Kumalasari (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
Every business, but particularly those in the industrial sector, have what is known as inventory. In order for the business to survive and carry on with production, inventory is crucial. Inventory control makes sure that products and resources don't run out of stock or become overstocked, which could lead to higher inventory costs and a halt in production. A business engaged in manufacturing is called PT. X. Hinge Upper Assy is one of the products that PT. X manufactures. Overproduction of raw materials caused issues for the hinge upper assembly material during the process, raising the overall cost of inventory. The EOQ (Economic Order Quantity) approach is one inventory control technique that determines overall inventory costs. The EOQ approach takes into account the frequency of orders, the amount of orders per order, safety stock, and reorder points in addition to inventory costs. The purpose of this study was to determine the overall cost of inventory at PT. X using the EOQ approach, as well as the frequency and quantity of orders, safety stock value, and reorder points. The study's findings indicate that the overall cost of inventory with EOQ is IDR 2,500,752.00, with a frequency of orders placed twice and a quantity per order of 20167 pieces, safety stock of 3242.28, and a reorder point of 3257 pieces. When comparing the EOQ approach to the company's traditional method, there was a 63% savings in total inventory expenses.